Strengthening Literacy Numeracy through Learning Trajectory Based on Realistic Mathematics Education in Elementary Schools - Siti Ruqoiyyah; Djuita Hidayati (Lembaga Bale Literasi, 2026)
Study This aim For increase literacy numeracy student school base through implementation learning trajectory based Realistic Mathematics Education (RME). Study This due to the low background ability literacy numeracy students shown? through results studies international as well as practice learning that is still ongoing nature conventional and less contextual . The method used is study action classes (PTK) that are implemented in two cycles , each covering stage planning , implementation , observation , and reflection . Subject study there are 29 students fourth grade school basis in West Lombok. Data collection was carried out through test literacy numeracy , observation activity students and teachers, as well as documentation . Data analyzed in a way quantitative and qualitative . Research results show existence improvement significant on literacy numeracy students . Completion classical increase from 68% in cycle I to 89% in cycle II. An increase also occurred in the indicators literacy numeracy , namely ability represent situation mathematics (82% to 87%), using problem-solving strategies problems (69% to 85%), as well reasoning and giving reasons (65% to 83%). In addition , the activity students and teachers improve to very good category . Findings This show that integration learning trajectory and RME capable create structured , contextual , and meaningful learning . Students No only understand draft mathematics , but also able to apply it in situation real